Edoardo Gellner - Le tende di Corte di Cadore - Romagnoli, Emiliano (Firenze Architettura, 2017)
“Traditional material culture” reveals a principle of survival of architecture from Cortina d’Ampezzo, centered on its only primordial element: shelter. From the Church of Cadore through a process of gemmation camping tents appear; small dormitory structures that reveal a rooted process of linguistic reduction. The work is expressed in a straightforward, yet subdued way, “so as not to overwhelm nature”.